UK shocks and Irish business cycles, 1922–791. (12th February 2018) - Stuart, Rebecca
Abstract: This article examines the transmission of UK and global shocks to the Irish economy over the period 1922–79, using annual data for consumer prices and real GDP in a structural vector autoregression (SVAR) model. UK aggregate demand and supply shocks have large and significant effects on Irish CPI, but smaller effects on Irish real GDP. A historical decomposition indicates that UK aggregate supply and demand shocks played a more important role than domestic shocks in the evolution of Irish CPI. In contrast, the evolution of Irish real GDP is driven more by idiosyncratic domestic shocks than by UK shocks.